Monitoring Area Coverage Based on Adjusting Node Spacing in Mixed Underwater Mobile Wireless Sensor Networks. (4th November 2022) - Li, Qiangyi; Liu, Ningzhong
Abstract : Wireless sensor nodes have the characteristics of small size, light weight, simple structure, and limited energy. They are random during deployment in the monitoring area, and the location of nodes is uncertain after deployment. It is easy to have uneven node distribution, resulting in dense nodes in some areas and sparse nodes in some areas. In the area with dense nodes, the monitoring area is covered repeatedly due to the distance between nodes which is too close. In the area with sparse nodes, the problem of covering blind areas appears due to the distance between nodes which is too far. Aiming at the complex structure of underwater wireless sensor networks, a coverage algorithm based on adjusting the nodes spacing is proposed. The algorithm calculates the reasonable distance between adjacent nodes before the wireless sensor node moves. The distance between wireless sensor nodes increases gradually. The simulation results show that the algorithm can make the clustered wireless sensor nodes disperse gradually by reasonably adjusting the distance between wireless sensor nodes, improve the coverage effect of wireless sensor networks, and reduce the energy consumption of wireless sensor nodes.